PENGARUH SISTEM PENGENDALIAN ANGGARAN BIAYA TERHADAP KINERJA MANAJER PERUSAHAAN KELAPA SAWIT DI PROPINSI KALIMANTAN SELATAN - Wahyu Sapto Rini (EKUITAS (Jurnal Ekonomi dan Keuangan), 2007)
This reserch’s target to know the level of system variable operation of budget which consist of compilation of program (X1), compilation of budget (X2), execution and measurement (X3), analysis and reporting (X4), clarity of budget and target(X5), and the difficulty level of budget (X6) to performance of manager measured with story; level efficiency of manager through eight evaluation criterion; planning, investigation of, coordination, election of staff, negotiation, representative, evaluation and observation. Analysis technique used to know the level of influence of system operation of budget which consist of six variabels to manager performance used doubled linear regression analysis. This research’s result succed to support the hypothesis, that is (X1), (X2), (X3), (X4), (X5), and (X6) by simultan have influence to manager performance. This matter means model of regression used in this research is good to progressively explain variation in manager performance. While conducted examination to second hypothesis giving result supporting the hypothesis. The result indicate that compilation of six variables have influence to manager performance by parsial.To be more improve manager performance, management should be more pay attention to manager participation level in course of compilation of budget, considering  this variable is biggest of influence to  manager performance, so that manager will be more productive because owning opportunity to develop the ability in the field of budgeting. Although contribution influence of clarity of budget target to variation in small manager performance relative, but to be more improve manager performance by top management remain to pay attention budget can always comprehend and presented detailedly, so that not generate difference of perception among executors of budget